2010
DOI: 10.1590/s0037-86822010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for physical disability at diagnosis of 19,283 new cases of leprosy

Abstract: Introduction: The purpose of this study was to evaluate risk factors for physical disability at the moment of leprosy diagnosis. Methods: This is a retrospective, descriptive and exploratory investigation of 19,283 patients with leprosy, registered in the State of Minas Gerais, Brazil, between 2000 and 2005. Results: The risk of Grade 2 disability was 16.5-fold higher in patients with lepromatous leprosy, and 12.8-fold higher in patients presenting the borderline form, compared to patients presenting indetermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
82
2
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 17 publications
19
82
2
22
Order By: Relevance
“…12,13 Although not signifi cant (p = 0.051), the results of this study suggest a higher level of education may contribute to the prevention of disabilities, an association which can be verifi ed with an increase in the number of cases analysed. Those with more time in the educational system, in addition to possibly having easier access to the health care system, may pay more attention to changes to their body, which may lead them to seek help earlier.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…12,13 Although not signifi cant (p = 0.051), the results of this study suggest a higher level of education may contribute to the prevention of disabilities, an association which can be verifi ed with an increase in the number of cases analysed. Those with more time in the educational system, in addition to possibly having easier access to the health care system, may pay more attention to changes to their body, which may lead them to seek help earlier.…”
Section: Discussionmentioning
confidence: 54%
“…5,13,17 Moschioni et al 13 (2010) showed that patients with the multibacillary form had a 5.7 greater chance of having disabilities compared to paucibacillary cases. This may be due to multibacillary cases being diagnosed later, which may favour the onset of disability, which is closely linked with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, neurological damage is among the main factors that contribute with physical inability, which makes systematic monitoring necessary 1,7 . However, there are important gaps in terms of operationalizing care to the people affected by leprosy at the post hospital discharge 8,9 .…”
Section: Palavras-chavementioning
confidence: 99%
“…Leprosy is considered an important public health problem due to its morbidity and socioeconomic impact, both of which are consequences of complications (e.g., physical disabilities and deformities) that develop during the clinical outcome of the disease [1][2][3]. Approximately 200,000 new cases are diagnosed annually worldwide, with the highest prevalence in intertropical developing countries such as India, Brazil, Myanmar, Madagascar, Nepal, and Mozambique [4].…”
Section: Introductionmentioning
confidence: 99%